p16 gene methylation in colorectal cancers associated with Duke′s staging - Yi, Jing (World J Gastroenterol, 2001)
AIM: To explore the association of methylation of the CpG island in the promotor of the P16 tumor suppressor gene with the clinicopathological characteristics of the colorectal cancers. METHODS: Methylation-specific PCR (MSP) was used to detect P16 methylation of 62 sporadic colorectal cancer specimens. RESULTS: P16 methylation was detected in 42% of the tumors. Dukes’ staging was associated with P16 methylation status. p16 methylation occurred more frequently in Dukes’ C and D patients (75.9%) than in Dukes’ A and B patients (12.1%). CONCLUSION: P16 methylation plays a role in the carcinogenes is of a subset of colorectal cancer, and it might be linked to poor prognosis.